Metal Adsorption in Batik Liquid Waste Using Adsorbents from Duck Eggshell and Durian Skin Waste - Huda, Muhammad Farkhan Fikri; Mustopa; Aktawan, Agus; Hakika, Dhias Cahya (Indonesian Journal of Chemical Engineering, 2025)
If industrial factory waste is directly disposed of into the surrounding environment, it can cause pollution, damaging the areas affected by the waste. Therefore, it is necessary to process the waste to reduce the harmful substances contained in the waste. This study conducted an experiment to reduce the metal content in batik liquid waste (Cu and Cd) using duck egg shells and durian peels as adsorbents. Before the production of activated charcoal, the duck egg shells and durian skins were washed and then sun-dried. Next, the duck egg shells are crushed into small granules, and the durian skins are cut into small pieces to facilitate carbonization. The carbonization process is carried out using a device called a furnace at a temperature of 600 °C for 2 hours for duck egg shells, and 300 °C for 1 hour for durian peels. Then, the obtained charcoal is ground and sieved using a 140 mesh sieve, followed by activation using a 4 N H3PO4 solution for 24 hours. The adsorption process is differentiated based on variations in contact time of 30, 90, and 180 minutes as the independent variable in the study, with adsorbent weight and stirring speed as the constant variables. After being analyzed using atomic absorption spectrophotometry, a reduction in Cu metal content by 27% and Cd metal content by 19% was obtained. The pH decreased from 13 to 10.